Factors influencing Employee Engagement in Public and Private Sector Banks in Chhattisgarh - VIJAYALAKSHMI, R.; CHANDRA, DR. ASHOK KUMAR; SOMA, MAHESH KUMAR (The journal of contemporary issues in business and government, 2021)
Employee involvement is regarded by many as a modern human resource strategy that helps companies to deal with volatile and turbulent market conditions. However, the research community in the banking industry is still searching for predictors of employee engagement. In Chhattisgarh, the banking sector is regarded as a place to work that respects the needs of each individual employee while also inspiring them to achieve their individual goals. The aim of this study was to highlight the needs of various individuals as well as the organization's expectations. Understanding generation Y (Gen Y) specific characteristics, desires, and aspirations, which are critical in today's context, is emphasised. Understanding how Gen Y workers act and what motivates them, as well as how they vary from Gen X employees, is a major focus. Better results are achieved by banks that are eager to understand their customers' needs and willing to support their employees' growth. A standardised questionnaire was used to collect data from 412 respondents in selected cities of public and private sector banks in Chhattisgarh. In addition, the element "work satisfaction" is used to examine individual personal differences in the organization's success.